Ophthalmologic Abnormalities in Children with Congenital Sensorineural Hearing Loss. Issue 3 (3rd July 2019) - Batson, Sean; Kelly, Katherine; Morrison, David; Virgin, Frank
ABSTRACT: Objective: To review a single center experience with the diagnosis of visual impairment in patients with sensorineural hearing loss (SNHL) and propose a diagnostic algorithm. Study Design: Retrospective study of patients with SNHL who were diagnosed with ophthalmologic abnormalities in the course of evaluation. Setting: University children's hospital and university-associated eye institute. Subjects and Methods: Children with the diagnosis of sensorineural hearing loss aged 0–18 who received a formal ophthalmology examination between the dates of December 2000-December 2016 were included for analysis. Children were identified using ICD-9 and ICD-10 billing codes. Primary measures included diagnosis of SNHL, ophthalmologic diagnoses, and referral source. Results: Two hundred and sixty-nine patients with SNHL met inclusion criteria. One hundred and thirty-one (48.5%) of these patients had an ophthalmic abnormality. When evaluating referral source, patients referred by a pediatrician following failed vision screen or visual complaint were more likely to have an ophthalmologic finding (61%, n = 147) when compared to referral by an otolaryngologist following diagnosis of SNHL (9.6%, n = 73). Seventeen of the 131 (13%) patients with at least one ophthalmic abnormality had an abnormality that was deemed unlikely to be detected by routine screening. Conclusion: Our study agreed with previously published works that there is a high rate of ophthalmic abnormalities in patients with SNHL. Evaluation of referral source for ophthalmology evaluation suggests that routine referral by otolaryngologists in patients with SNHL may not be an efficient means of identifying patients with treatable ophthalmic disease. Reliance on school and office screenings to detect ophthalmic abnormalities, prior to referral, is likely a more efficient model, even among patients with SNHL.